2015
DOI: 10.1104/pp.114.255562
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chloroplast Protein Import without Tic56, a Component of the 1-Megadalton Translocon at the Inner Envelope Membrane of Chloroplasts

Abstract: We report on the characterization of Tic56, a unique component of the recently identified 1-MD translocon at the inner envelope membrane of chloroplasts (TIC) in Arabidopsis (Arabidopsis thaliana) comprising Tic20, Tic100, and Tic214. We isolated Tic56 by copurification with Tandem Affinity Purification-tagged Toc159 in the absence of precursor protein, indicating spontaneous and translocation-independent formation of the translocon at the outer envelope membrane of chloroplasts (TOC) and TIC supercomplexes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 72 publications
4
66
0
Order By: Relevance
“…This approach has already proven useful in the identification of TIC56 in a TOC159-containing super complex (17). Here, we identify KOC1 as a new component in this complex and show that it is required for full import activity and successful de-etiolation.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…This approach has already proven useful in the identification of TIC56 in a TOC159-containing super complex (17). Here, we identify KOC1 as a new component in this complex and show that it is required for full import activity and successful de-etiolation.…”
mentioning
confidence: 89%
“…The 1MD complex associates with the translocating preprotein and forms a preprotein sensitive channel when reconstituted into planar lipid bilayers. TIC components (both absent and present in the 1 MD complex) co-purified with TOC159 suggesting that they cooperate in preprotein import (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…the development of the thylakoids). For example, mutations in TOC159 and TIC56 (Köhler et al, 2015) result in chlorotic seedlings and plastids with reduced and disorganized internal membranes. Mutations in components of a secondary destination translocase (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This system includes the Tic20 paralog Tic20-IV in Arabidopsis but lacks Tic56, Tic100, and Tic214 (Hirabayashi et al, 2011;Kikuchi et al, 2013;Parker et al, 2014;Nakai, 2015). Experimental data shown in recent work by Kö hler et al (2015) provide support for this model of more than one TIC complex. They found that the major TIC complex containing Tic56 shows very strong physical interaction with the major TOC complex containing the Toc159 receptor.…”
Section: How Can We Explain the Evolutionary History Of Ycf1 Includimentioning
confidence: 72%